A lithium-ion battery
Patent Information
- Application Number
- CN202611384043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-27
AI Technical Summary
(1)本申请创新性地提出一种正负极界面调控+阻燃电解液体系协同配合的设计,在稳定正极材料结构、稳定SEI膜的同时降低电池热失控的风险,提高了电池的循环性能和安全性,1C/1C循环500次容量保持率≥92.1%,优选≥93.9%,针刺测试中,电池无起火、爆炸现象。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This application belongs to the field of lithium-ion battery technology and relates to a lithium-ion battery. Background Technology
[0002] Traditional lithium-ion batteries often face two major technical challenges in energy storage system applications: First, the cell cycle life is reduced, which is caused by the reaction between the electrode and electrolyte interface to form an unstable SEI film, and by the destruction of the positive electrode structure stability during multiple cycles. Second, traditional liquid electrolytes have flammable properties and are prone to thermal runaway under abuse scenarios such as puncture and compression.
[0003] Some related technologies disclose methods to stabilize the SEI film by adding film-forming additives to the electrolyte. For example, CN110148783A discloses an electrolyte for improving the performance of the SEI film on the surface of a graphite electrode, its preparation method, and its application. The electrolyte includes an organic solvent, a film-forming additive, and a solute salt. The organic solvent includes a cyclic carbonate solvent, and the film-forming additive includes a fluorocarbonate. The total molar concentration of the solute salt in the solvent is maintained at 3 mol / L. The solute salt includes a mixture of lithium salt and an ionic liquid, with a molar ratio of lithium salt to ionic liquid of 2:1. The lithium salt is lithium di(trifluoromethanesulfonyl)imide, and the ionic liquid is N-methyl-N-propenylpiperidine di(trifluoromethanesulfonyl)imide. When applied to a graphite / lithium half-cell, this electrolyte can form a denser and more stable SEI film on the surface of the graphite electrode, improving the cycle performance of the battery. For example, CN116979149A discloses an electrolyte additive for batteries, an electrolyte comprising the additive, and a battery. The electrolyte additive contains a sulfate ester compound, the chemical formula of which is: Wherein, R1 is selected from halogen atoms, and R2, R3, and R4 are each independently selected from one or more of hydrogen atoms, halogen atoms, C1-C6 alkyl groups, or C1-C6 fluoroalkyl groups. The electrolyte additive of this application can form a stable SEI film and reduce battery side reactions.
[0004] However, by adding film-forming additives to the electrolyte, the film-forming additives may coexist with other components in the electrolyte, which may inhibit the effect of other components, leading to a decline in the overall performance of the electrolyte. Moreover, it cannot change the problem that liquid electrolytes are flammable and prone to thermal runaway.
[0005] Therefore, providing a lithium-ion battery that can achieve both excellent cycle life and reduce the risk of battery thermal runaway is a technical problem that urgently needs to be solved.
[0006] Application content To address the aforementioned technical problems in the existing technology, the purpose of this application is to provide a lithium-ion battery. This application, through the control of the positive and negative electrode interface and the adjustment of the electrolyte formulation, can improve the safety and controllability of the battery while stabilizing the positive electrode material structure and SEI, resulting in a lithium-ion battery with a longer service life and better safety performance.
[0007] To achieve the above objectives, this application adopts the following technical solution: This application provides a lithium-ion battery, including a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode material, which comprises a positive electrode active material and an atomic deposition layer disposed on the surface of the positive electrode active material. The atomic deposition layer includes Al2O3 and ZrO2. The negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode material and a composite film-forming agent, which comprises fluoroethylene carbonate and ethylene sulfate. The oxygen index of the electrolyte is ≥28%.
[0008] In the lithium-ion battery of this application, the oxygen index of the electrolyte is ≥28%, for example, it can be 28%, 29%, 30%, 31% or 32%, etc. However, it is not limited to the listed values, other unlisted values within this range are also applicable.
[0009] This application innovatively proposes a design that combines positive and negative electrode interface regulation with a flame-retardant electrolyte system to stabilize the positive electrode material structure and SEI film while reducing the risk of battery thermal runaway. The technical principle is as follows: First, by depositing an atomic deposition layer on the surface of the positive electrode active material and forming a composite coating using Al2O3 and ZrO2, compared to the method of mixing Al2O3 and ZrO2 as oxide particles with the positive electrode active material and then sintering, the coating layer is dense and uniform, which can inhibit the dissolution of transition metal ions in the positive electrode active material, reduce side reactions with the electrolyte, and improve the structural stability of the positive electrode material. Furthermore, the synergistic combination of Al2O3 and ZrO2 through atomic deposition, compared to a single type, exhibits superior corrosion resistance and interface stability, better inhibiting the dissolution of transition metal ions while reducing interfacial impedance and improving the structural integrity of the positive electrode material. Secondly, by adding a composite film-forming agent to the negative electrode active layer, the composite film-forming agent preferentially forms a thin and dense SEI film on the negative electrode surface during the first charge and discharge cycle. This film can reduce interfacial impedance and inhibit lithium dendrite growth. Moreover, compared to adding a film-forming agent to the electrolyte, it can also avoid competition between the film-forming agent and other components in the electrolyte, thus avoiding a reduction in the overall performance of the electrolyte. Thirdly, the electrolyte of this application has an oxygen index ≥28%, which can reduce the risk of battery thermal runaway and ensure the safety of the battery under abuse conditions.
[0010] The synergistic solution for electrode interface modification and electrolyte formulation optimization proposed in this application requires no additional equipment, has strong process compatibility, and can be directly used in existing lithium-ion battery production lines without increasing industrialization costs.
[0011] In some embodiments, the molar ratio of Al2O3 to ZrO2 is (1~5):(1~5), wherein the range of Al2O3 is "1~5", for example, it can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5, and the range of ZrO2 is "1~5", for example, it can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5, etc. However, it is not limited to the listed values; other unlisted values within this range are also applicable.
[0012] In some embodiments, the thickness of the atomically deposited layer is 5 nm to 10 nm, for example, it can be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm. However, it is not limited to the listed values; other unlisted values within this range are also applicable. Within this range, the increase in impedance can be minimized while maintaining the structural stability of the positive electrode active material.
[0013] In some embodiments, the chemical formula of the positive electrode active material is Li. a Ni x Co y A z M b O2, wherein A is Mn or Al, M is at least one of Al, Mg, Zr, Ti, W, Nb, Y, and Ga, and 0.8 <a<1.3,0.8≤x<1,0<y<1,0<z<1,x+y+z+b=1,0≤b<0.2。
[0014] In some embodiments, the mass ratio of fluoroethylene carbonate (FEC) to vinyl sulfate (DTD) is (1~3):(1~3), wherein the range of fluoroethylene carbonate is "1~3", for example, it can be 1, 1.5, 2, 2.5 or 3, etc.; the range of vinyl sulfate is "1~3", for example, it can be 1, 1.5, 2, 2.5 or 3, etc. However, it is not limited to the listed values, and other unlisted values within this range are also applicable. The mass ratio of fluoroethylene carbonate to vinyl sulfate in the composite film-forming agent falls within the above-mentioned preferred range. If there is too little fluoroethylene carbonate and too much vinyl sulfate, it will lead to an increase in SEI film impedance, deteriorating rate performance and cycle performance; if there is too much fluoroethylene carbonate and too little vinyl sulfate, it will lead to an overly porous SEI film, unable to effectively inhibit lithium dendrite growth, and a decrease in cycle performance.
[0015] In some embodiments, the composite film-forming agent accounts for 0.5 wt% to 1 wt% of the mass of the negative electrode active layer, for example, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, or 1 wt%. However, it is not limited to the listed values; other unlisted values within this range are also applicable. If the content of the composite film-forming agent is too low, it will result in incomplete SEI film coverage, increased interfacial side reactions, and decreased cycle performance. If the content of the composite film-forming agent is too high, it will result in an excessively thick interfacial film, increasing lithium-ion transport impedance and reducing capacity utilization and cycle performance.
[0016] In some embodiments, the electrolyte includes an organic solvent, a lithium salt, and a flame retardant.
[0017] In some embodiments, the organic solvent includes dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), wherein the volume percentage of dimethyl carbonate in the organic solvent is 40% to 60% (e.g., 40%, 42%, 45%, 47%, 50%, 53%, 56%, 58%, or 60%), and the volume percentage of ethyl methyl carbonate in the organic solvent is 40% to 60% (e.g., 40%, 42%, 45%, 47%, 50%, 53%, 56%, 58%, or 60%). However, this is not limited to the listed values; other unlisted values within this range also apply. If the volume percentage of dimethyl carbonate is too high, it will lower the flash point of the electrolyte, affecting safety; if the volume percentage of ethyl methyl carbonate is too high, it will increase the viscosity of the electrolyte and reduce ionic conductivity.
[0018] In some embodiments, the lithium salt comprises lithium bis(trifluorosulfonyl)imide.
[0019] In some embodiments, the lithium salt accounts for 0.2 wt% to 0.5 wt% of the mass of the electrolyte, for example, 0.2 wt%, 0.3 wt%, 0.4 wt%, or 0.5 wt%. However, it is not limited to the listed values; other unlisted values within this range are also applicable.
[0020] In some embodiments, the flame retardant includes triethyl phosphate.
[0021] In some embodiments, the flame retardant has a mass percentage of 5wt% to 10wt% in the electrolyte, for example, it can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, or 10wt%.
[0022] By limiting the types and contents of organic solvents, lithium salts, and flame retardants in the electrolyte of this application, the electrolyte can have high ionic conductivity, good compatibility with positive and negative electrodes, suitable viscosity and interfacial wettability, and good flame retardancy.
[0023] Compared with existing technologies, this application has the following advantages: (1) This application innovatively proposes a design that combines positive and negative electrode interface regulation with flame-retardant electrolyte system. While stabilizing the positive electrode material structure and SEI film, it reduces the risk of battery thermal runaway and improves the battery's cycle performance and safety. The capacity retention rate after 500 cycles of 1C / 1C is ≥92.1%, preferably ≥93.9%. In the nail penetration test, the battery does not catch fire or explode.
[0024] (2) The synergistic solution of electrode interface modification and electrolyte formulation optimization proposed in this application does not require additional equipment, has strong process compatibility, can be directly used in existing lithium-ion battery production lines, and will not increase industrialization costs. Detailed Implementation
[0025] The technical solution of this application will be further described below through specific implementation methods.
[0026] The specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application.
[0027] In this embodiment of the application, the oxygen index of the electrolyte is a key indicator for measuring the flame retardancy and fire resistance of the electrolyte. It refers to the minimum volume fraction of oxygen required for the electrolyte to maintain stable and flaming combustion in an oxygen-nitrogen mixed gas flow under specified test conditions, and the unit is _____.
[0028] Example 1 This embodiment provides a lithium-ion battery, including a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode current collector (copper foil) and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode material (graphite), a thickener (sodium carboxymethyl cellulose), a first binder (styrene-butadiene rubber), and a composite film-forming agent. The mass ratio of the negative electrode material, thickener, first binder, and composite film-forming agent is 96:2:1.5:0.5. The composite film-forming agent includes fluoroethylene carbonate (FEC) and ethylene sulfate (DTD), and the mass ratio of FEC to DTD is 1:1.
[0029] The positive electrode comprises a positive current collector (aluminum foil) and a positive active layer disposed on the surface of the positive current collector. The positive active layer comprises a positive electrode material, a conductive agent (conductive carbon black), and a second binder (polyvinylidene fluoride). The mass ratio of the positive electrode material, the conductive agent, and the second binder is 95:3:2. The positive electrode material comprises a positive active substance (chemical formula LiNi).0.8 Co 0.1 Mn 0.1 O2) and a coating layer disposed on the surface of the positive electrode active material, wherein the coating layer is an atomic deposition layer with a thickness of 8 nm, and the atomic deposition layer is an Al2O3-ZrO2 composite coating (wherein, the molar ratio of Al2O3 and ZrO2 is 1:1).
[0030] The electrolyte comprises an organic solvent, a lithium salt, and a flame retardant. The organic solvent is a mixture of dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1. The lithium salt is lithium bis(trifluorosulfonyl)imide (LiTFSI), which accounts for 0.3 wt% of the volume in the electrolyte. The flame retardant is triethyl phosphate (TEP), which accounts for 10 wt% of the mass in the electrolyte. The oxygen index of the electrolyte is 28%.
[0031] This embodiment also provides a method for preparing the above-mentioned lithium-ion battery, including the following steps: (1) Cathode preparation: LiNi was prepared by ALD technology. 0.8 Co 0.1 Mn 0.1 The surface of the O2 material is coated with an 8nm Al2O3-ZrO2 composite coating, and then mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:3:2 to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil, dried, and rolled to form a positive electrode sheet. (2) Anode preparation: Graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, FEC and DTD are mixed evenly in a mass ratio of 96:2:1.5:0.25:0.25 to obtain anode slurry. The anode slurry is coated on copper foil, dried and rolled to form anode sheet. (3) Electrolyte preparation: Mix DMC and EMC at a volume ratio of 1:1 to obtain an organic solvent. Add 10wt% TEP and 0.3wt% LiTFSI to the organic solvent and stir until completely dissolved to form a homogeneous solution to obtain the electrolyte. (4) Battery assembly: The positive electrode, negative electrode and polypropylene separator are stacked to form an electrode group, electrolyte is injected, and after encapsulation, a soft-pack cell is made, which is a lithium-ion battery.
[0032] In the preparation method of this embodiment, there is no time-bound order of the interdependence between steps (1), (2), and (3), and those skilled in the art can select them as needed.
[0033] Example 2 This embodiment provides a lithium-ion battery, including a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode current collector (copper foil) and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode material (graphite), a thickener (sodium carboxymethyl cellulose), a first binder (styrene-butadiene rubber), and a composite film-forming agent. The mass ratio of the negative electrode material, thickener, first binder, and composite film-forming agent is 96:2.5:1:1. The composite film-forming agent includes fluoroethylene carbonate (FEC) and ethylene sulfate (DTD), and the mass ratio of FEC to DTD is 3:1.
[0034] The positive electrode comprises a positive current collector (aluminum foil) and a positive active layer disposed on the surface of the positive current collector. The positive active layer comprises a positive electrode material, a conductive agent (conductive carbon black), and a second binder (polyvinylidene fluoride). The mass ratio of the positive electrode material, the conductive agent, and the second binder is 95:3:2. The positive electrode material comprises a positive active substance (chemical formula LiNi). 0.8 Co 0.1 Mn 0.1 O2) and a coating layer disposed on the surface of the positive electrode active material, wherein the coating layer is an atomic deposition layer with a thickness of 5 nm, and the atomic deposition layer is an Al2O3-ZrO2 composite coating (wherein, the molar ratio of Al2O3 and ZrO2 is 1:5).
[0035] The electrolyte comprises an organic solvent, a lithium salt, and a flame retardant. The organic solvent is a mixture of dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 2:3. The lithium salt is lithium bis(trifluorosulfonyl)imide (LiTFSI), which accounts for 0.2 wt% of the volume in the electrolyte. The flame retardant is triethyl phosphate (TEP), which accounts for 6 wt% of the mass in the electrolyte. The oxygen index of the electrolyte is 32%.
[0036] This embodiment also provides a method for preparing the above-mentioned lithium-ion battery, including the following steps: (1) Cathode preparation: LiNi was prepared by ALD technology. 0.8 Co 0.1 Mn 0.1 The surface of the O2 material is coated with a 5nm Al2O3-ZrO2 composite coating, and then mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:3:2 to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil, dried, and rolled to form a positive electrode sheet. (2) Anode preparation: Graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, FEC and DTD are mixed evenly in a mass ratio of 96:2.5:1:0.5:0.5 to obtain anode slurry. The anode slurry is coated on copper foil, dried and rolled to form anode sheet. (3) Electrolyte preparation: Mix DMC and EMC at a volume ratio of 2:3 to obtain an organic solvent. Add 6 wt% TEP and 0.2 wt% LiTFSI to the organic solvent and stir until completely dissolved to form a homogeneous solution to obtain the electrolyte. (4) Battery assembly: The positive electrode, negative electrode and polypropylene separator are stacked to form an electrode group, electrolyte is injected, and after encapsulation, a soft-pack cell is made, which is a lithium-ion battery.
[0037] In the preparation method of this embodiment, there is no time-bound order of the interdependence between steps (1), (2), and (3), and those skilled in the art can select them as needed.
[0038] Example 3 This embodiment provides a lithium-ion battery, including a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode current collector (copper foil) and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode material (graphite), a thickener (sodium carboxymethyl cellulose), a first binder (styrene-butadiene rubber), and a composite film-forming agent. The mass ratio of the negative electrode material, thickener, first binder, and composite film-forming agent is 96:2:1.5:0.8. The composite film-forming agent includes fluoroethylene carbonate (FEC) and ethylene sulfate (DTD), and the mass ratio of FEC to DTD is 1:3.
[0039] The positive electrode comprises a positive current collector (aluminum foil) and a positive active layer disposed on the surface of the positive current collector. The positive active layer comprises a positive electrode material, a conductive agent (conductive carbon black), and a second binder (polyvinylidene fluoride). The mass ratio of the positive electrode material, the conductive agent, and the second binder is 95:2.5:2.5. The positive electrode material comprises a positive active material (chemical formula LiNi). 0.8 Co 0.1 Mn 0.1 O2) and a coating layer disposed on the surface of the positive electrode active material, wherein the coating layer is an atomic deposition layer with a thickness of 10 nm, and the atomic deposition layer is an Al2O3-ZrO2 composite coating (wherein the molar ratio of Al2O3 and ZrO2 is 5:1).
[0040] The electrolyte comprises an organic solvent, a lithium salt, and a flame retardant. The organic solvent is a mixture of dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 3:2. The lithium salt is lithium bis(trifluorosulfonyl)imide (LiTFSI), which accounts for 0.5 wt% of the volume in the electrolyte. The flame retardant is triethyl phosphate (TEP), which accounts for 9 wt% of the mass in the electrolyte. The oxygen index of the electrolyte is 30%.
[0041] This embodiment also provides a method for preparing the above-mentioned lithium-ion battery, including the following steps: (1) Cathode preparation: LiNi was prepared by ALD technology. 0.8 Co 0.1 Mn 0.1 The surface of the O2 material is coated with a 10nm Al2O3-ZrO2 composite coating, and it is mixed evenly with conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:2.5:2.5 to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil, dried, and rolled to form a positive electrode sheet. (2) Anode preparation: Graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, FEC and DTD are mixed evenly in a mass ratio of 96:2:1.5:0.4:0.4 to obtain anode slurry. The anode slurry is coated on copper foil, dried and rolled to form anode sheet. (3) Electrolyte preparation: Mix DMC and EMC at a volume ratio of 3:2 to obtain an organic solvent. Add 9 wt% TEP and 0.5 wt% LiTFSI to the organic solvent and stir until completely dissolved to form a homogeneous solution to obtain the electrolyte. (4) Battery assembly: The positive electrode, negative electrode and polypropylene separator are stacked to form an electrode group, electrolyte is injected, and after encapsulation, a soft-pack cell is made, which is a lithium-ion battery.
[0042] In the preparation method of this embodiment, there is no time-bound order of the interdependence between steps (1), (2), and (3), and those skilled in the art can select them as needed.
[0043] Example 4 The difference between this embodiment and Embodiment 1 is that in the Al2O3-ZrO2 composite coating, the molar ratio of Al2O3 to ZrO2 is 1:6.
[0044] Example 5 The difference between this embodiment and Embodiment 1 is that in the Al2O3-ZrO2 composite coating, the molar ratio of Al2O3 to ZrO2 is 6:1.
[0045] Example 6 The difference between this embodiment and Embodiment 1 is that the mass ratio of fluoroethylene carbonate to ethylene sulfate in the composite film-forming agent is 1:4.
[0046] Example 7 The difference between this embodiment and Example 1 is that the mass ratio of fluoroethylene carbonate to ethylene sulfate in the composite film-forming agent is 4:1.
[0047] Example 8 The difference between this embodiment and Embodiment 1 is that the composite film-forming agent accounts for 0.4 wt% of the mass of the negative electrode active layer.
[0048] Example 9 The difference between this embodiment and Embodiment 1 is that the composite film-forming agent accounts for 1.1 wt% of the mass of the negative electrode active layer.
[0049] Example 10 The difference between this embodiment and Example 1 is that the content of TEP is increased from 10wt% to 11wt%, and the total mass percentage of organic solvent in this embodiment is reduced by 1wt% compared to Example 1.
[0050] Comparative Example 1 The difference between this comparative example and the embodiment is that, in the positive electrode preparation step, LiNi was not processed. 0.8 Co 0.1 Mn 0.1 The electrode is coated with O2 material; no fluoroethylene carbonate or ethylene sulfate is added to the negative electrode slurry; no TEP or LiTFSI is added to the electrolyte, but 1 mol / L of LiPF6 is added to the electrolyte.
[0051] Comparative Example 2 The difference between this comparative example and the embodiment is that fluoroethylene carbonate and ethylene sulfate were not added to the negative electrode slurry.
[0052] Comparative Example 3 The difference between this comparative example and Example 1 is that the TEP content in the electrolyte is reduced from 10 wt% to 0 wt%, and the total mass percentage of organic solvent in this comparative example is increased by 10 wt% compared to Example 1. The oxygen index of the electrolyte in this comparative example is 20%.
[0053] Comparative Example 4 The difference between this comparative example and Example 1 is that, in the positive electrode preparation step, LiNi was not processed. 0.8 Co 0.1 Mn 0.1 The material is coated with O2.
[0054] Comparative Example 5 The difference between this comparative example and Example 1 is that, in the cathode preparation step, the Al2O3-ZrO2 composite coating is formed by: mixing Al2O3 particles, ZrO2 particles, and LiNi... 0.8 Co 0.1 Mn 0.1 After mixing with O2 materials, the mixture is sintered at 400℃ for 3 hours.
[0055] Performance testing: (1) Capacity retention rate after 500 1C / 1C cycles: Charge-discharge cycles were performed at a 1C rate for 500 cycles. The first discharge capacity C1 and the 500th discharge capacity C were recorded. 500 And calculate the capacity retention rate after 500 cycles of 1C / 1C, using the formula: C 500 / C1×100%.
[0056] (2) Needle penetration test: The lithium-ion battery is subjected to a needle penetration test under full charge, and the needle penetration position is the geometric center of the lithium-ion battery.
[0057] The test results are shown in Table 1. As shown in Table 1, this application, through the synergistic design of positive and negative electrode interface control and flame-retardant electrolyte system, reduces the risk of battery thermal runaway while stabilizing the positive electrode material structure and SEI film. This improves the battery's cycle performance and safety, achieving a capacity retention rate of ≥92.1% (preferably ≥93.9%) after 500 1C / 1C cycles. During the nail penetration test, the battery showed no signs of fire or explosion, indicating excellent service life and safety performance.
[0058] Comparative Example 1 did not coat the positive electrode active material, did not modify the interface of the negative electrode, and used a conventional electrolyte, resulting in a capacity retention rate of only 89.4% after 500 cycles of 1C / 1C, and it also caught fire during the needle penetration test.
[0059] Compared to Example 1, Comparative Example 2 did not perform interface modification on the negative electrode. Due to the lack of composite film-forming agent, the SEI film of the negative electrode was unstable, resulting in a decrease in cycle performance to 91.2%.
[0060] Comparative Example 3 did not add flame retardant TEP to the electrolyte, which has a flammable problem, causing the battery cell to catch fire during the needle penetration test, and thus failing to meet the requirements of practical applications.
[0061] The comparison between Example 1 and Comparative Examples 4-5 shows that by coating the positive electrode active material, especially by coating Al2O3 and ZrO2 in the form of atomic deposition, the structure of the material can be better stabilized and the cycle performance can be improved.
[0062] A comparison of Examples 1 and 4-5 shows that there is an optimal range for the molar ratio of Al2O3 and ZrO2. If there is too little Al2O3 and too much ZrO2 (Example 4), the corrosion resistance of the composite coating will decrease, the interfacial impedance will increase, and the cycle retention rate will decrease to 92.6%. If there is too much Al2O3 and too little ZrO2 (Example 5), the coating will not be dense enough and will not be able to effectively inhibit the dissolution of metal ions, and the cycle retention rate will decrease to 92.9%.
[0063] A comparison of Examples 1 and 6-7 shows that there is an optimal range for the mass ratio of fluoroethylene carbonate to vinyl sulfate. If there is too little fluoroethylene carbonate and too much vinyl sulfate (Example 6), the SEI membrane impedance will increase and the cycle retention rate will decrease to 92.2%. If there is too much fluoroethylene carbonate and too little vinyl sulfate (Example 7), the SEI membrane will be too porous and the cycle retention rate will decrease to 92.5%.
[0064] A comparison of Examples 1 and 8-9 shows that there is an optimal range for the mass ratio of the composite film-forming agent in the negative electrode active layer. If the mass ratio of the composite film-forming agent is too small (Example 8), the SEI film will not be fully covered, and the cycle retention rate will decrease to 92.1%. If the mass ratio of the composite film-forming agent is too large (Example 9), the interface film will be too thick, and the cycle retention rate will be 92.4%.
[0065] A comparison between Example 1 and Example 10 shows that if the content of flame retardant is too high, it will reduce the ionic conductivity of the electrolyte, reduce the cycle retention rate to 93.7%, and increase the cost.
[0066] The applicant declares that this application illustrates the detailed method of this application through the above embodiments, but this application is not limited to the above detailed method, that is, it does not mean that this application must rely on the above detailed method to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the raw materials of this application's product, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.
Claims
1. A lithium-ion battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The positive electrode includes a positive electrode material, which includes a positive electrode active material and an atomic deposition layer disposed on the surface of the positive electrode active material. The atomic deposition layer includes Al2O3 and ZrO2. The negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode material and a composite film-forming agent. The composite film-forming agent includes fluoroethylene carbonate and ethylene sulfate. The oxygen index of the electrolyte is ≥28%.
2. The lithium-ion battery according to claim 1, characterized in that, The molar ratio of Al2O3 to ZrO2 is (1~5):(1~5).
3. The lithium-ion battery according to claim 1 or 2, characterized in that, The thickness of the atomic deposition layer is 5 nm to 10 nm.
4. The lithium-ion battery according to any one of claims 1-3, characterized in that, The chemical formula of the positive electrode active material is Li a Ni x Co y A z M b O2, wherein A is Mn or Al, M is at least one of Al, Mg, Zr, Ti, W, Nb, Y, and Ga, and 0.8 <a<1.3,0.8≤x<1,0<y<1,0<z<1,x+y+z+b=1,0≤b<0.2。 5. The lithium-ion battery according to any one of claims 1-4, characterized in that, The mass ratio of the fluoroethylene carbonate to the ethylene sulfate is (1~3):(1~3).
6. The lithium-ion battery according to any one of claims 1-5, characterized in that, The composite film-forming agent has a mass percentage of 0.5wt% to 1wt% in the negative electrode active layer.
7. The lithium-ion battery according to any one of claims 1-6, characterized in that, The electrolyte contains organic solvents, lithium salts, and flame retardants.
8. The lithium-ion battery according to claim 7, characterized in that, The organic solvent includes dimethyl carbonate and ethyl methyl carbonate, wherein the volume percentage of dimethyl carbonate in the organic solvent is 40% to 60%, and the volume percentage of ethyl methyl carbonate in the organic solvent is 40% to 60%.
9. The lithium-ion battery according to claim 7 or 8, characterized in that, The lithium salt comprises lithium bis(trifluorosulfonylimide); and / or, The lithium salt accounts for 0.2wt% to 0.5wt% of the mass of the electrolyte.
10. The lithium-ion battery according to any one of claims 7-9, characterized in that, The flame retardant includes triethyl phosphate; and / or, The flame retardant accounts for 5 wt% to 10 wt% of the mass of the electrolyte.
Citation Information
Patent Citations
Electrolyte for improving performance of SEI film on surface of graphite electrode, preparation method thereof and application thereof
CN110148783A